Understanding the evolving nature of novel psychoactive substances: Mapping 10 years of research - Alessandro Carollo; Ornella Corazza; Olivier Rabin; Aurora Coppola; Gianluca Esposito (Elsevier, 2023)
Novel psychoactive substances (NPS) is an umbrella term used to describe a heterogeneous group of compounds that mimic the effects of existing drugs and whose demand and use rapidly emerge, change, or even vanish in the drug market. The novelty of this global phenomenon and its dynamic nature represent major challenges for the scientific community that constantly requires timely evidence-based inputs. Our aim is to review the literature on NPS and compare its temporal evolution according to the topics presented at the International Conference series on NPS over the past decade. Our analysis shows that some new clusters of research recently emerged in comparison to a previous review and that the material presented at the NPS Conferences anticipates the scientific literature by approximately 2.5 years. Such findings not only provide new original insights on the latest NPS trends but also address existing knowledge gaps in the NPS field, while emphasizing the importance of face-to-face thematic events supported by faster publication processes to inform prompt interventions and policy making.